Beyond tit-for-tat in cyberspace: Political warfare and lateral sources of escalation online. (June 2020) - Whyte, Christopher
Abstract: At present, most scholarship on the potential for escalation in cyberspace couches analysis in terms of the technological dynamics of the domain for relative power maneuvering. The result has been a conceptualisation of the logic of operation in cyberspace as one of 'tit-for-tat' exchanges motivated by attribution problems and limited opportunity for strategic gain. This article argues that this dominant perspective overlooks alternative notions of how cyber tools are used to influence. This, in turn, has largely led scholars to ignore second-order effects – meaning follow-on effects triggered by a more direct outcome of an initial cyber action – on domestic conditions, institutions, and individual stakeholders. This article uses the case of cyber-enabled political warfare targeting the United States in 2016 to show how escalation can occur as a second-order effect of cyber operations. Specifically, the episode led to a re-evaluation of foreign cyber strategy on the part of American defence thinkers that motivated an offensive shift in doctrine by 2018. The episode also directly affected both the political positions taken by important domestic actors and the attitude of parts of the electorate towards interference, both of which have reinforced the commitment of military planners towards assertive cyber actions.